Educação léxico-gramatical: um estudo semântico-enunciativo da preposição com - Vilela, Thatiana Ribeiro [UNIFESP] (2016)
Developed within the field of Enunciation Linguistics, this research seeks to contribute to the design of reflective pedagogical proposals which target the teaching and learning of morphosyntax via a semantic-enunciative study of the Portuguese preposition COM. It starts with a linguistic description of COM which can both encompass its different syntactic functions, and explain its varied discourse meanings. It will also try to identify typical formations, connected to particular uses, which better help comprehend the role it has in the construction of meaning in the utterances it is part of. The research is based on the Theory of Enunciative Operations (CULIOLI, 1990; DE VOGÜÉ, FRANCKEL, PAILLARD, 2011), and, mainly, on the works of Franckel & Paillard (2007) focusing the semantics of prepositions.